Akulturasi Klenteng Berkubah di Kota Bandung Tahun 2020 - Marshanda Suci Meisya; Ading Kusdiana (UIN Sunan Gunung Djati Bandung, 2022)
Acculturation in places of worship in Bandung is a very rare thing. Culture is a symbolic tool for controlling attitudes so that cultural processes must be understood, translated and interpreted. Bandung is one of the cities that has cultural acculturation with Chinese ethnicity.The existen ce of Chinese ethnicity in the city of Bandung began to be seen when the construction of mosques in Chinese style by adding very close Chinese elements, namely the Al-Imtizaj Mosque and Lautze 2 Mosque in Bandung City.